AES characterization of protective thin layers on the AgNiO.15 contact material after its treatment in the RF plasma - Koller, Lidija (Informacije MIDEM, 1999)
Well-known surface protection of Ag-contacts with the thin gold layer is rather expensive. We studied some cheaper types of protective layers. Thickness of the layer must be optional to avoid the corrosion effect of the surroundings and at the same time to insure sufficiently good electric conductivity between the two coated surfaces. Material that is used for the layers must be at least as good electric conductor as the ground material unless the contact characteristics deteriorate. Protection of contact surfaces is therefore a compromise between the increase of the contact stability and the deterioration of the initial contact characteristics. Three different protective lavers were depisited on the AgNiO.15 contact material. After their treatment in the radio frequency plasma they were analyzed with the Auger spectrometer
Keywords: električni kontakti; nikelj; pasivacija; spektroskopija; srebro